2012
DOI: 10.7314/apjcp.2012.13.5.2269
|View full text |Cite
|
Sign up to set email alerts
|

Health-promoting Lifestyle Behaviour for Cancer Prevention: a Survey of Turkish University Students

Abstract: Background: Health risks associated with unhealthy behaviours in adolescent and university students contribute to the development of health problems in later life. During the past twenty years, there has been a dramatic increase in public, private, and professional interest in preventing disability and death through changes in lifestyle and participation in screening programs. The aim of the study was to evaluate university students' health-promoting lifestyle behaviour for cancer prevention. Method: This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 9 publications
2
29
0
1
Order By: Relevance
“…Similar studies also support these results (Can et al, 2008;Ay et al, 2012;Al-Naggar et al, 2013;Ozveren H et al, 2013).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar studies also support these results (Can et al, 2008;Ay et al, 2012;Al-Naggar et al, 2013;Ozveren H et al, 2013).…”
Section: Discussionsupporting
confidence: 78%
“…In those studies (Walker et al, 1988;Unalan et al, 2007;Al Kandari et al, 2008;Kreutz et al, 2009;Ay et al, 2012), it is found that consciousness of health increases with age. The reason we found contradicting results with this study may be associated with the stress and responsibilities of the medical students with rising ages.…”
Section: Discussionmentioning
confidence: 95%
“…In other studies where the behaviors of students with regard to protection from cancer were examined, similar results were reached (19,33,34). The findings of our study may have risen form reasons such as most of the students residing in dormitories, the students spending most of their day at school, and the insufficiency of sports fields.…”
Section: Does Familial History Of Cancer Affect the General Health Cosupporting
confidence: 73%
“…Perceived health status was achieved by asking, "How do you evaluate your health conditions at the moment?" (good, average, bad) (15). …”
Section: Methodsmentioning
confidence: 99%